Clinical relevance of KRAS in human cancers - Jancík, Sylwia; Drábek, Jirí; Radzioch, Danuta; Hajdúch, Marián (Journal of biomedicine & biotechnology, 2010)
The KRAS gene (Ki-ras2 Kirsten rat sarcoma viral oncogene homolog) is an oncogene that encodes a small GTPase transductor protein called KRAS. KRAS is involved in the regulation of cell division as a result of its ability to relay external signals to the cell nucleus. Activating mutations in the KRAS gene impair the ability of the KRAS protein to switch between active and inactive states, leading to cell transformation and increased resistance to chemotherapy and biological therapies targeting epidermal growth factor receptors. This review highlights some of the features of the KRAS gene and the KRAS protein and summarizes current knowledge of the mechanism of KRAS gene regulation. It also underlines the importance of activating mutations in the KRAS gene in relation to carcinogenesis and their importance as diagnostic biomarkers, providing clues regarding human cancer patients' prognosis and indicating potential therapeutic approaches.
Keywords: Proto-Oncogene Proteins; protoonkogenní proteiny; nádory; Ras proteiny; ras Proteins; Humans; lidé; Proto-Oncogene Proteins p21(ras); protoonkogenní proteiny p21(ras); Neoplasms